Efeitos da fragmentação florestal sobre as assembleias de peixes de igarapés da zona urbana de Manaus, Amazonas - Anjos, Helio Daniel Beltrão dos (Instituto Nacional de Pesquisas da Amazônia - INPA, 2007)
The city of Manaus is growing in an accelerated and disordered way, what provokes the fragmentation of the forest and condemns the urban streams to the disappearance. With those streams, an important portion of the local aquatic biodiversity gets lost, before even of being appropriately known. We studied the stream fish assemblages in 15 urban forest fragments, seeking to evaluate the effects of the forest fragmentation and structural characteristics of the streams on the composition and diversity of the ictiofauna. 41 species of fish were collected, of six orders and 11 families. Species richness varied from one to 14 species in 200m stream reaches. Streams subjected to anthropogenic impacts presented conspicuous changes in limnological parameters and in the composition and structure of the assemblies of fish as well. Preserved streams contained richer fish assemblages, associated to high values of dissolved oxygen and low values of conductivity and pH, whereas the inverse situation was registered in streams polluted by domestic sewage. The similarity in the composition of fish assemblages was not correlated significantly with the linear distance among the fragments, neither with the hydrological connectivity among the streams. Differences in the original environmental characteristics of the streams, as well as the subsequent isolation of populations of fish for chemical barriers (highly polluted streams among the forest fragments) can be responsible for the differences now observed in the composition of species in nearby streams. The species richness found in each stream (1-14 species) was small in relation to the overall species richness found (41 species), indicating a high Beta diversity. Such results indicate that the conservation of the forest fragments of the urban area of Manaus is critical for the maintenance of the general fish diversity, once the fragments contain different subsets of regional ichthyofauna. Therefore, the destruction of any fragment may result in the local extinction of one or more species of fish, with an important loss of the regional biodiversity.
Keywords: Ecologia de igarapés; Ictiofauna; Amazônia; Impactos antropogênicos